The latin language and medical terminology. Part I. Anatomical terminology: methodological manual for teachers - Kulichenko, A.; Titiyevska, T.; Kalashnikova, M.; Martianova, M.; Куліченко, Алла Костянтинівна; Тітієвська, Тетяна Василівна; Калашникова, Марина Юріївна; Мартьянова, Марія Євгеніївна (Запорізький державний медичний університет, 2019)
The methodological manual for teachers who conduct practical classes for the first-year students of the medical faculties with the English medium of instruction contains the detailed plans of the discipline “The Latin Language and Medical Terminology”, speciality 222 “General Medicine”. The aim of the methodological manual is to assist the teachers with the organization of learning process for the first-year students with the English medium of instruction.
Латинська мова та медична термінологія. Ч. І. Анатомічна термінологія